(untitled) (Praxis Educativa, 2016)
Given the importance that journalistic discourse acquires in actual societies and the role given to university students as critical subjects of reality, this research, based on sociocultural and critical perspectives of reading and on the concepts of media education and media competence, aims to determine what are the difficulties that show admitted students in Humanities from a public university in Argentina to interact with texts from the press. To do it we stop at the analysis -mainly qualitative- of the answers to a test of understanding of a text of opinion published in a national newspaper. Partial results allow us to emphasize the need to develop strategies that encourage critical reading of media at the university level and to enrich the media competence of students as individuals committed to social issues.